The Role of Instagram as an Agent for Socialization in Integrated Islamic School at SMP IT Abu Bakar Yogyakarta: A Netnography Study - Risuhawianto, Irwan; Yuliana, Lia (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2025)
In the digital era, social media platforms have become essential tools for educational institutions to communicate, engage, and shape public perception. This study explores the role of Instagram as an agent of socialization within the context of an Integrated Islamic School, specifically SMP IT Abu Bakar Yogyakarta. This type of research is descriptive-qualitative using a netnography approach. This research analyzes the visual and textual content posted on the school’s Instagram account, along with user interactions such as comments and likes, to understand how values, identity, and community norms are constructed and transmitted in a digital space. Findings indicate that Instagram functions beyond mere promotion; it actively contributes to the process of value internalization among students, parents, and prospective stakeholders. The platform serves as a medium for reinforcing Islamic identity, showcasing school culture, and facilitating participatory engagement that reflects the broader educational mission of the institution. Through curated content and interactive features, the school extends its influence into the digital realm, transforming Instagram into a space of informal yet meaningful socialization. This study highlights the evolving role of social media in contemporary Islamic education and emphasizes the need for intentional and value-driven digital communication strategies. It also presents a novel application of netnography in analyzing religious educational contexts, contributing to the understanding of how traditional institutions adapt to digital environments while maintaining their ideological foundations.